Asian development outlook 2018 supplement the outlook remains stable. - Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2018)
Developing Asia is seen to maintain growth projections at 6.0% for 2018 and 5.9% for 2019. However rise in protectionist trade measures from other countries poses a clear downside risk to the regions outlook.Developing Asia is largely on track to meet growth expectations as set out in April in Asian Development Outlook 2018 (ADO 2018). The regional gross domestic product (GDP) is forecast to expand by 6.0% in 2018 and 5.9% in 2019, the rate envisaged in April, with subregional forecasts upgraded for Central Asia. Regional growth forecasts are maintained at 6.5% for 2018 and 6.4% for 2019 when excluding the newly industrialized economies of Hong Kong, China; the Republic of Korea; Singapore; and Taipei,China. The combined growth forecast for the major industrial economies the United States (US), the euro area, and Japan is retained from ADO 2018 as growth in the US and the euro area remains robust. In Japan, though, unanticipated contraction in the first quarter (Q1) prompts a slight revision of the 2018 growth.
Keywords: Development economics -- Asia; Electronic books